2013
DOI: 10.25100/rc.v16i0.510
|View full text |Cite
|
Sign up to set email alerts
|

Estudio De La Adsorción De Plomo En Suelos De La Región Minera En El Distrito De Buenos Aires En El Departamento Del Cauca, Colombia.

Abstract: Se realizaron isotermas de adsorción para determinar el equilibrio de distribución de plomo en los suelos del área de influencia de la mina La Vetica, ubicada en el distrito minero de Buenos Aires en el Departamento del Cauca, con el fin de determinar su capacidad de adsorción y retención. Se evaluaron dos modelos de adsorción: el primero asume que el fenómeno se presenta en la primera capa superficial (superficie homogénea) tal como la describe los modelos de Langmuir, Dubinin-Radushkevich y Frumkin; y el seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, it should be noted that Kaolinite and Humus, when added to the soil, can be inferred that these types of interactions increase, giving an increase in the adsorption processes for Atrazine and Trifluralin. In addition, it should be noted that the adsorption of these two pesticides on Kaolinite occurs clearly on its surface, which has been studied in various works 51,52 , due to the difference in polarity between the molecule and the faces of the Kaolinite, not being possible an internal adsorption in the structure of this one. Ce [mg L -1 ]…”
Section: Kd and Koc Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it should be noted that Kaolinite and Humus, when added to the soil, can be inferred that these types of interactions increase, giving an increase in the adsorption processes for Atrazine and Trifluralin. In addition, it should be noted that the adsorption of these two pesticides on Kaolinite occurs clearly on its surface, which has been studied in various works 51,52 , due to the difference in polarity between the molecule and the faces of the Kaolinite, not being possible an internal adsorption in the structure of this one. Ce [mg L -1 ]…”
Section: Kd and Koc Parametersmentioning
confidence: 99%
“…In addition, it has been reported through other studies that the presence of allophanic clays and organic carbon content determine a greater persistence or adsorption of Atrazine in soils 51 . However, there are many more studies on the determination of the half-life of Atrazine in the soil worldwide, where values between 54 -56 days have been found in soils of Brazil 52 , while in soils from Minnesota was found that after 16 months, Atrazine and its degradation products were still present in the soil, with a potential for mobility that can contaminate groundwater 53 .…”
Section: Persistence Of Atrazine and Trifluralinementioning
confidence: 99%